Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve for [tex]\( x \)[/tex].

[tex]\[ 6(1+5x) = 5(1+6x) \][/tex]


Sagot :

Certainly! Let's solve the equation [tex]\(6(1 + 5x) = 5(1 + 6x)\)[/tex] step-by-step:

1. Distribute the constants on both sides of the equation:

On the left side:
[tex]\[ 6(1 + 5x) = 6 \cdot 1 + 6 \cdot 5x = 6 + 30x \][/tex]

On the right side:
[tex]\[ 5(1 + 6x) = 5 \cdot 1 + 5 \cdot 6x = 5 + 30x \][/tex]

Now, your equation looks like this:
[tex]\[ 6 + 30x = 5 + 30x \][/tex]

2. Move the variable term [tex]\(30x\)[/tex] to both sides to isolate the constants:

Subtract [tex]\(30x\)[/tex] from both sides of the equation:
[tex]\[ 6 + 30x - 30x = 5 + 30x - 30x \][/tex]

Simplifying this, we get:
[tex]\[ 6 = 5 \][/tex]

3. Analyze the resulting statement:

The statement [tex]\(6 = 5\)[/tex] is clearly false. This indicates that there is a contradiction without any variable involvement. Therefore, there are no values of [tex]\(x\)[/tex] that can satisfy the original equation.

Hence, the final conclusion is:
[tex]\[ \boxed{The \, equation \, 6(1 + 5x) = 5(1 + 6x) \, has \, no \, solution.} \][/tex]